Genetic Characterizr: tion of three Ompok species using mitochondrial DNA sequences
Partial sequences of cytochrome b (Cyt b) and 16S ribosomal RNA 16S rRNA mitochondrial genes were used for species identification and estimating phylogenetic relationship among three commercially important Ompok species viz. 0. pabda/ 0. pabo & 0. bimaculatus. The sequence analysis of Cyt b 1118bp) and 16S rRNA 569 & 570bp) genes revealed that 0. pabda1 0. pabo & 0. bimacu/atus were genetically distinct species and they exhibited identical phylogenetic relationship. The present study discussed usefulness of mtDNAgenes Cyt b & 16S rRNA) in resolving taxonomic ambiguity and estimating phylogenetics relationship. Keywords: Ompok; mtDNA gene; Cyt b; 16S rRNA; Genetic variation. , journal=Journal of Indian Fisheries Association, author=Malakar, A. K. and Lakra, W. S. and Singh, M. and Goswami, M. and Mishra, R. M., year=2009, month=Dec.